Inhibition of Inducible Nitric Oxide Synthase and Cyclooxygenase-2 by Gamijihwang-tang Via Suppression of Nuclear Factor-B Activation in RAW 264.7 cells - Du Hyun Jang; Ji Young Kim; Eun Hee Han; Hee Ok Park; Dong Hee Kim; Hye Gwang Jeong; Dong Yeol Yoo (동의생리병리학회지, 2005)
Asthma is recognized today as an inflammatory disease of the lung characterized by acute non-specific airway hypersensitiveness in association with chronic pulmonary inflammation. Gamijihwang-tang(GJT), a fortified prescription of YMJHT, is applied for the treatments of chronic coughing and asthma, and post-delivery coughing and asthma in the gynecology. Also in the clinical practice, GJT is known to be very effective for controlling coughing and asthma as a cold sequela. In this study, we investigated the effects of GJT on the lipopolysaccharide (LPS)-induced nitric oxide (NO) and prostaglandin E2 (PGE2) production, and on the level of inducible nitric oxide synthase (iNOS) and Cyclooxygenase-2 expression in murine macrophage RAW 264.7 cells. We found that GJT inhibited LPS-induced NO and PGE2 production in a dose dependent manner. Furthermore, GJT inhibited the expression of LPS-induced iNOS and COX-2 protein and mRNA expression in RAW 264.7 macrophages. Treatment with GJT of RAW 264.7 cells transfected with a reporter construct indicated a reduced level of LPS-induced nuclear factor-κB (NF-κB) activity and effectively lowered NF-κB binding as measured by transient transfection assay. These results suggest that the main inhibitory mechanism of the GJT may be the reduction of iNOS and COX-2 gene expression through blocking of NF-κB activation. KCI Citation Count: 0